Identification of Land Surface Temperature Regarding Land Use Utilizing Landsat 8 OLI Imagery in 2021 (Case Study: Padang City Area, West Sumatra Province) - Putri, Sri Kandi; Pertiwi, Mentari Dian; Ameiliya, Nandha; Anggita, Sekha; Noveraliza, Yessy (CV Bumi Spasial, 2024)
This research of aims are; 1) identify the Land Surface Temperature (LST) of land use using Landsat 8 OLI imagery for the Padang City area, 2) identify the distribution of land use using Landsat 8 OLI imagery for the Padang City area, 3) The effect of Land Surface Temperature (LST) on land use using Landsat 8 OLI imagery for the Padang City area. In obtaining the results of Land Use researchers used the Indonesian National Standard (SNI) 7645-2020 Classification of Land Cover Scale 1: 250,000. Meanwhile, to get the surface temperature value using the LST (Land Surface Temperature) method. The results of land use analysis obtained 10 classes, namely settlements, airports, mining, built-up land, settlements, fields, rice fields, shrubs and shrubs, secondary forests, and rivers. LST (Land Surface Temperature) results obtained 8 temperature classes including the lowest temperature, which is around 19.38ᵒC and the highest temperature 33.17ᵒC.